(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2023)
This article focuses on the participation of light as an active element in the visual characterization of the performer. It addresses its transformative potential in the metamorphosis of the artist’s appearance during a live show. For this, we draw a parallel between the trajectory of two artists/designers: Loïe Fuller (1862-1928), choreographer/dancer, multimedia artist who worked in the design of light and clothing, and Robert Wilson (1941), director and actor who is obsessively dedicated to the control of light and the precise use of this element in the scenic space of live shows. We ended the study with the analysis of three works (with audiovisual recordings) that relate in some way to the two artists studied.